TEACHING ENGLISH LANGUAGE CHALLENGES AMONG BEGINNER ENGLISH TEACHERS AT SECONDARY SCHOOLS IN JORDAN - Mouaweya Mohammad Abed Abdelghani; Ahmad Taufik Hidayah Abdullah, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This study investigates the difficulties faced by novice English teachers in Jordanian secondary schools, focusing on the impact of errors made by new teachers on the academic performance of (EFL ) students. The research used interviews and observation to gather data, with purposive sampling strategies employed. The results showed that novice EFL teachers needed to focus more on lesson overviews, presenting topics in a logical order, explaining major and minor points clearly, providing explanations for complex or challenging topics, and providing definitions of terms and concepts. The primary language challenges faced by novice teachers were pronunciation, listening comprehension, and grammar. 40% of teachers did not connect lessons together, and 45% needed to deliver lesson themes in a logical order. Only 30% of inexperienced teachers focused on emphasizing the lesson's essential elements, while 60% needed to. 65% of new teachers needed to clearly articulate important and small ideas, while 30% needed more attention on offering definitions of terms, concepts, and principles. 60% of new teachers needed to provide clear examples to illustrate lessons and put steps into practice while solving homework difficulties. The study suggests that the native tongue of EFL beginning teachers, irregularities in sound, diverse grammar forms, tenses, and vocabulary size account for most of these challenges. Socio-psycho variables, such as attitude, anxiety, and self-confidence, also impact these teachers. To address these challenges, it is crucial to set uniform standards for all schools and conduct further research on the root causes of these challenges.